Application of real-time quantitative PCR assays for detecting marine Brucella spp. in fish. (January 2018) - Norman, Stephanie A.; Delaney, Martha A.; Haman, Katherine H.; Thomas, Austen C.; Godfroid, Jacques; Larsen, Anett K.; Nymo, Ingebjørg H.; Robbe-Austerman, Suelee; Quance, Christine; Rhyan, Jack C.; Lambourn, Dyanna M.; Jeffries, Steven J.; et al.
Brucella ceti and Brucella pinnipedialis have been documented as occurring in marine mammals, and B. ceti has been identified in 3 naturally acquired human cases. Seroconversion and infection patterns in Pacific Northwest harbor seals ( Phoca vitulina richardii ) and North Atlantic hooded seals ( Cystophora cristata ) indicate post-weaning exposure through prey consumption or lungworm infection, suggesting fish and possibly invertebrates play an epizootiologic role in marine Brucella transmission and possible foodborne risk to humans. We determined if real-time quantitative PCR (qPCR) assays can detect marine Brucella DNA in fish DNA. Insertion sequence (IS) 711 gene and sequence type (ST)27 primer–probe sets were used to detect Brucella associated with marine mammals and human zoonotic infections, respectively. First, DNA extracts from paired-species fish (containing 2 species) samples were tested and determined to be Brucella DNA negative using both IS 711 and ST27 primer–probe sets. A representative paired-species fish DNA sample was spiked with decreasing concentrations of B. pinnipedialis DNA to verify Brucella detection by the IS 711 primer–probe within fish DNA. A standard curve, developed using isolated DNA from B. pinnipedialis, determined the limit of detection. Finally, the IS 711 primer–probe was used to test Atlantic cod ( Gadus morhua ) DNA extracts experimentally infected with the B. pinnipedialis hooded seal strain. In culture-positive cod tissue, the IS 711 limit of detection was ~1 genome copy of Brucella . Agreement between culture and PCR results for the 9 positive and 9 negative cod tissues was 100%. Although a larger sample set is required for validation, our study shows that qPCR can detect marine Brucella in fish.